Comparison of Coronally Advanced Flap with Semilunar Coronally Repositioned Flap with Sutures for the Treatment of Gingival Recession - Rana, Sweta Rajya Laxmi; Shrestha, Surendra Man; Pradhan, Ameena (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: The surgical correction of shallow gingival recession by coronally advanced flap (CAF) and its variant semilunar coronally repositioned flap (SLF) offers the advantage of a single surgical site, less patient discomfort and predictable root coverage with good colour match. This study aims to compare and evaluate the predictability and reliability of the two types of flaps. Methods: In 20 Miller’s Class I recession defects, 10 sites each were treated with either SLF or CAF. Recession height, recession width, clinical attachment loss, width of keratinized gingiva, Plaque Index and Gingival Index were assessed at baseline, 1, 3 and 6 months. The intra-group comparison was done using paired t-test and the inter-group comparison using independent t-test with statistical p value set at <0.05. Results: Average root coverage seen with Group I (SLF) at 1 month was 51.67% and with Group II (CAF) was 62.5% and at 6 months the root coverage was 42.5% for both the groups. In both Groups, statistically significant changes in recession width and recession height were seen from baseline to 6 months. No statistically significant difference was seen between the two groups at any time period. Conclusions: The coronally advanced flap is predictable in the treatment of gingival recessions. However the semilunar flap with additional stabilizing suture may also be beneficial in treating gingival recessions and further research is needed in this technique.